NogoA-expressing astrocytes limit peripheral macrophage infiltration after ischemic brain injury in primates - Anthony G. Boghdadi (Nature Portfolio, 2021)
Astrocytes are important players in ischemic stroke. Here, the authors use single nuclei transcriptomics to characterise marmoset astrocytes following brain injury. At functional level, they show that NogoAexpressing astrocytes limit macrophage infiltration.